Assessing Rural-Urban Differences in Screening for Mental Health Needs Among Individuals in County Jails - Nelson, Victoria (International journal of offender therapy and comparative criminology, 2025)
Rural jails are increasingly contributing to the overall jail population and little is known about how they differ from non-rural jails. This study compares demographic, behavioral health and criminal/legal histories of 3,797 individuals who booked into three rural jails and seven non-rural jails. In addition, the study assessed how jails identify mental illness, which was compared to an objective screening instrument (Kessler-6). Individuals in rural jails were more likely to be white, female, have a history of mental health services, misuse substances, and to recidivate. After controlling for these differences, they had 1.5 times greater odds of having a mental illness but lower odds of being identified by the jails. Individuals in rural jails have more behavioral health needs and other criminogenic risk factor and their needs are less likely to be identified by jail staff, which may result in poor connection to diversion or treatment opportunities.